ELABORATION AND DIELECTRIC CHARACTERIZATION OF A DOPED FERROELECTRIC MATERIAL TYPE PZT - M. Abba; Z. Necira; N. Abdessalem; A. Meklid; H. Menasra; A. Boutarfaia (Journal of Fundamental and Applied Sciences, 2015)
The main objective of this work is based on the synthesis and dielectric characterization of a new material in ceramic PZT with a perovskite structure ABO3. We are interested to study the Quaternary system (doping in site A and site B) of general formula: Pb0.96Ba0.02Ca0.02[(Zr0.52Ti0.48)0.94(Zn1/3Ta2/3)0.03(In1/3Sb2/3)0.03]O3 short PZT-PBC-ZTIS. The sample selected for this study was prepared by the method of synthesis with solid way. Heat treatment was applied to these compositions at different temperatures: 1100, 1150,1180 and 1200 °C successively to optimize the sintering temperature optimal where the density of the sample is maximum (near theoretical density) and therefore the product has better physical quality. The study of dielectric properties of all samples showed a high permittivity dielectric εr = 18018, low dielectric loss: tgδ = 7.62%, for the composition sintered to 1180 ° C included in the phase morphotropique zone (FMP).